Evaluation of p-Amidinophenyl Esters as Potential Antithrombotic Agents - Pizzo, Salvatore V; Turner, Denise; Porter, Ned A; Gonias, Steven L (Thrombosis and Haemostasis, 1986)
Three p-amidinophenyl esters have been synthesized and characterized as irreversible inhibitors of the vitamin-K dependent proteinases; factors IXa, Xa and thrombin (Turner et al. [4])+. In the present report we describe the in vitro and in vivo effects of these agents on standard coagulation tests in vitro and in blood from animals treated with the compounds. At a concentration of 500 μM, the three esters increased the activated partial thromboplastin time (PTT) of pooled human plasma 3 to 5-fold. The prothrombin time increased 1.4 to 3.7-fold under similar conditions. The p-amidinophenyl ester of cinnamic acid (CINN) showed the most pronounced effect on both assays. This ester also is the best inhibitor of human factors IXa and Xa, while the p-amidinophenyl ester of benzoic acid (BENZ) is a slightly better α-thrombin inhibitor (4). The effect of these esters on the thrombin clotting time correlated with in vitro kinetic measurements of α-thrombin inhibition rates. Both BENZ and CINN increased the assay endpoint more than 6-fold. The three esters also were studied using mouse plasma. A comparable effect on the PTT was noted. Intravenous administration of 300 αl of 1 mM CINN as a single bolus in mice caused a 2.3-fold increase in the PTT which remained 1.2-fold normal 2 h later. The BENZ and a-methyl-cinnamic acid (MECINN) esters were somewhat less effective as predicted from their in vitro effect on the PTT. This investigation and previous studies indicate that these compounds demonstrate low toxicity at therapeutic levels. It is concluded that the p-amidinophenyl esters may be useful in antithrombotic therapy.
Keywords: p-Amidinophenyl esters; Proteinase inhibitors; Vitamin-K dependent proteinases